Relationships between glide efficiency and swimmers' size and shape characteristics - Naemi, R.; Psycharakis, S. G.; McCabe, C.; Connaboy, C.; Sanders, R. H. (Journal of Applied Biomechanics, 2012)
Glide efficiency, the ability of a body to minimize deceleration over the glide, can change with variations in the body`s size and shape. The purpose of this study was to investigate the relationships between glide efficiency and the size and shape characteristics of swimmers. Eight male and eight female swimmers performed a series of horizontal glides at a depth of 70 cm below the surface. Glide efficiency parameters were calculated for velocities ranging from 1.4 to 1.6 m/s for female swimmers (and at the Reynolds number of 3.5 million) and from 1.6 to 1.8 m/s for male swimmers (and at the Reynolds number of 4.5 million). Several morphological indices were calculated to account for the shape characteristics, with the use of a photogrammetric method. Relationships between the variables of interest were explored with correlations, while repeated-measures ANOVA was used to assess within-group differences between different velocities for each gender group. Glide efficiency of swimmers increased when velocity decreased. Some morphological indices and postural angles showed a significant correlation with glide efficiency. The glide coefficient was significantly correlated to the chest to waist taper index for both gender groups. For the male group, the glide coefficient correlated significantly to the fineness ratio of upper body, the chest to hip cross-section. For the female group the glide coefficient had a significant correlation with the waist to hip taper index. The findings suggested that gliding efficiency was more dependent on shape characteristics and appropriate postural angles rather than being dependent on size characteristics.